Evaluation of Three Botanicals, Bavistin and BAU-Biofungicide for Controlling Leaf Spot of Groundnut Caused by Cercospora arachidicola and Cercosporidium personatum - Hossain, MH; Hossain, I (The Agriculturists, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> A study was conducted to evaluate the effectiveness of three selected botanicals namely leaf extract of Neem (Azadirachta indica), Debdaru (Polyalthia longifolia) and datura (black) (Datura metel) along with Bavistin (Carbendazim) and BAU-biofungicide (Trichoderma harzianum) against leaf spot disease (tikka) of groundnut caused by Cercospora arachidicola and Cercosporidium personatum at the Field Research Farm of Bangladesh Agricultural University, Mymensingh during 2009-10. The most effective treatments were Bavistin, BAU-biofungicide (seed treatment + spray), BAU-biofungicide (spray) and leaf extract of Neem. Bavistin increased pod and dry haulm yield by 53.51 and 24-80 %, respectively. Maximum pod yield and dry haulm weight were recorded under Bavistin. BAU-biofungicide (seed treatment + spray) produced the second highest pod and dry haulm yield followed by leaf extract of Neem and BAU-biofungicide (spray). BAU-biofungicide (seed treatment + spray) and leaf extract of Neem may be recommended for controlling leaf spot disease of groundnut. DOI: http://dx.doi.org/10.3329/agric.v12i1.19579 <span style="font-size: 12.0pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: "Times New Roman"; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Times New Roman"; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The Agriculturists <span style="font-size: 11.0pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: "Times New Roman"; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Times New Roman"; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">2014<span style="font-size: 12.0pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: "Times New Roman"; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Times New Roman"; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">; 1<span style="font-size: 11.0pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: "Times New Roman"; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Times New Roman"; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">2(1) 41-49<!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->